Liquid Mixing Enhancement by PLC-Based Chaotic Dynamics Implementation - Abdulkareem, Hamzah; Rahma, Fadhil; Radhi, Jawad (Iraqi Journal for Electrical and Electronic Engineering, 2019)
In this paper, we present a new programmable chaotic circuit based on the dynamical chaotic system introduced by E. Lorenz. The design and realization of the model are accomplished by using a programmable logic controller (PLC). The system can be modeled and realized with a structured texted. The nonlinear differential equations of Lorenz model are solved numerically. The generated chaotic signal by using PLC is applied to a single- phase induction motor via a variable frequency drive to create a chaotic perturbation in the experiments of liquid mixing. Colorization liquid experiments shows that the generated chaotic motion effectively makes an enhancement of the mixing process in the stirred-tank mixer model in our laboratory.